Health care systems engineering : HCSE, Florence, Italy, May 2017 - Cappanera, Paola ; Li, Jingshan ; Matta, Andrea ; Sahin, Evren ; Vandaele, Nico J. ; Visintin, Filippo (Springer, 2020)
This book presents statistical processes for health care delivery and covers new ideas, methods and technologies used to improve health care organizations. It gathers the proceedings of the Third International Conference on Health Care Systems Engineering (HCSE 2017), which took place in Florence, Italy from May 29 to 31, 2017. The Conference provided a timely opportunity to address operations research and operations management issues in health care delivery systems. Scientists and practitioners discussed new ideas, methods and technologies for improving the operations of health care systems, developed in close collaborations with clinicians. The topics cover a broad spectrum of concrete problems that pose challenges for researchers and practitioners alike: hospital drug logistics, operating theatre management, home care services, modeling, simulation, process mining and data mining in patient care and health care organizations. Intro; Foreword Proceedings HCSE 2017; Preface; Contents; Contributors; Regular Contributions; 1 How to Protect a Hospital Against Cyber Attacks; Abstract; 1 Introduction; 2 The Cyber Attack Sources; 2.1 Hacktivists; 2.2 Terrorists; 2.3 Criminals or State Sponsored Hackers; 3 The Cyber Attack Approach; 3.1 The Information System Mapping as a Tool; 3.2 The Critical Assets; 3.3 The Critical Asset Attractiveness; 3.4 The Threat Scenarios; 4 The Scenario Assessment with the Information System Mapping; 4.1 The Strongly Connected Components of the Information System; 4.2 The K Partitioning Problem Contents: 4.3 Feedback of Partitioning by Scenario5 Conclusion; References; Analytical Approaches to Operating Room Management; 1 Introduction; 2 Surgical Case Length Prediction; 3 Improving Operational Efficiency of the Perioperative Process; 4 Post-Anesthesia Care Unit Scheduling; 5 Discussion; References; A New Decomposition Approach for the Home Health Care Problem; 1 Introduction; 2 Problem Statement and Related Work; 3 Methodology; 3.1 Stage 1: Route First; 3.2 Stage 2: Solving the Assignment Problem; 3.3 Obtaining the Operational Routes; 4 Data Generation and Preliminary Experiments Contents: 5 Conclusion and PerspectivesReferences; 4 Strategic Operations Management in Healthcare: A Reference Model for Cardiac Rehabilitation; Abstract; 1 Introduction; 2 Methodology; 3 Literature Review and Definition of the Theoretical Model; 3.1 Internal Factors; 3.2 External Factors; 4 Results from the Case Study; 5 Towards a Reference Model for Strategic Operations Management in Healthcare; 6 Conclusion; Acknowledgements; References; Mining the Patient Flow Through an Emergency Department to Deal with Overcrowding; 1 Introduction; 2 A Case Study; 2.1 Patient Population Contents: 2.2 Retrospective Analysis3 Process Modelling; 3.1 Preprocessing; 3.2 Process Discovery; 3.3 Patient Clustering; 4 Conclusions; References; A Location Problem for Medically Under-Served Areas in Korea; 1 Introduction; 2 Problem Description; 2.1 Operational Definitions for MUA; 2.2 Location Model; 3 Case: MUA Support Program in Korea for Obstetrics Care; 3.1 Case Illustration; 3.2 Results; 4 Conclusion; References; A Choice Model for Estimating Realized Accessibility: Case Study for Obstetrics Care in Korea; 1 Introduction; 2 Discrete Choice Model Contents: 3 Choice Model for Obstetrics Patients in Korea3.1 Model Components; 3.2 Data; 4 Result; 5 Conclusion; References; Handling Time-Related Demands in the Home Care Nurse-to-Patient Assignment Problem with the Implementor-Adversarial Approach; 1 Introduction; 1.1 Related Works; 2 Nurse-to-Patient Assignment Problem; 3 The Robust Optimization Approach; 3.1 Uncertainty Set; 3.2 Robust Model; 3.3 Implementor-Adversarial Algorithm; 4 Computational Tests and Results; 5 Conclusions; References; A Cardinality-Constrained Robust Approach for the Ambulance Location and Dispatching Problem